On asymptotically exact estimates for the approximation of certain classes of functions by algebraic polynomials - Motornaya, O. V.; Motornyi, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We present a survey of results obtained for the last decade in the field of approximation of specific functions and classes of functions by algebraic polynomials in the spaces C and L 1 and approximation with regard for the location of a point on an interval.